Book reviews: “Saeed Zakeri, A Course in Complex Analysis”, Princeton University Press, 2021, xii+428 pages, hardback, ISBN: 9780691207582, ebook, ISBN: 9780691218502. - IANCU, Mihai (Studia Universitatis Babeș-Bolyai Mathematica, 2022)
The book under review is an excellent introduction to Complex Analysis.The author managed to put together in a harmonious way a large variety of classical results of the theory. Here is a list with the most important topics and results with complete self-contained proofs in the book: